Indigenous Language Revitalization and Applied Linguistics: Conceptualizing an Ethical Space of Engagement Between Academic Fields - Daniels, Belinda; Sterzuk, Andrea (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
This conceptual paper examines the relationship between two academic areas: applied linguistics and Indigenous language revitalization. While the two domains have shared interests, they tend to operate separately. This paper examines: 1) possible reasons for this separateness; 2) mutually beneficial reasons to be in closer conversation and 3) changes necessary for the creation of an ethical space of engagement (Ermine, 2007) between these academic areas. We write from distinct positions: Belinda, a nēhiyaw woman working in Indigenous language resurgence and Andrea, a white settler woman working in language issues related to settler-colonialism. Drawing from our joint and individual experiences, we explore how these research fields can complement each other as well as intersect to create richer interdisciplinary knowledge.